2021
DOI: 10.3390/epidemiologia2030030
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 Vaccination Strategy in China: A Case Study

Abstract: The coronavirus disease 2019 (COVID-19) outbreak in China was first reported to the World Health Organization on 31 December 2019, after the first cases were officially identified around 8 December 2019. However, the case of an infected patient of 55 years old can probably be traced back on 17 November. The spreading has been rapid and heterogeneous. Economic, political and social impacts have not been long overdue. This paper, based on English, French and Chinese research in national and international databas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 77 publications
0
3
0
Order By: Relevance
“…Similar observations were reported in Jordan and Malaysia, where there was low uptake of the COVID-19 vaccine (El-Elimat et al, 2021;Mohamed et al, 2021). On the contrary, in countries such as China and Spain, findings revealed that a majority of the populace, including older adults, had completed the full course of the COVID-19 vaccine (Iguacel et al, 2021;Mohamadi et al, 2021;Ontario Agency for Health Protection and Promotion, 2021;Zheng et al, 2021).…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…Similar observations were reported in Jordan and Malaysia, where there was low uptake of the COVID-19 vaccine (El-Elimat et al, 2021;Mohamed et al, 2021). On the contrary, in countries such as China and Spain, findings revealed that a majority of the populace, including older adults, had completed the full course of the COVID-19 vaccine (Iguacel et al, 2021;Mohamadi et al, 2021;Ontario Agency for Health Protection and Promotion, 2021;Zheng et al, 2021).…”
Section: Discussionsupporting
confidence: 67%
“…Despite instances of hesitancy documented in countries such as Jordan, Russia, France, Hungary, and Portugal (El-Elimat et al, 2021;Lindholt et al, 2021;Soares et al, 2021), other countries, including the United States (US), China, Saudi Arabia, Malta, Mozambique, Malaysia, Denmark, and Germany, among others, have displayed positive attitudes toward the vaccine (Al-Mohaithef & Padhi, 2020;Dula et al, 2021;Lazarus et al, 2020;Lindholt et al, 2021;Mohamed et al, 2021;Reiter et al, 2020;Graeber et al, 2021). Moreover, research indicates that a significant proportion of populations in China, Canada, Spain, and other countries has already received a full dose of the COVID-19 vaccine (Iguacel et al, 2021;Mohamadi et al, 2021;Ontario Agency for Health Protection and Promotion, 2021;Zheng et al, 2021). Gender, education level, age, employment status, residence, knowledge about the vaccine, course of study, influence of significant others, and concerns about vaccine safety all emerge as significant variables influencing attitudes toward the COVID-19 vaccine (Bai et al, 2021;Cordina et al, 2021;El-Elimat et al, 2021;Rzymski et al, 2021).…”
Section: International Journal Of Population Studiesmentioning
confidence: 99%
“…Interviews were conducted in December 2020 when China reported 104 domestic COVID-19 cases, a 76.3% increase compared to November 2020 ( The State Council, 2020 ). Over the course of data collection, the first domestically produced COVID-19 vaccine was granted conditional marketing authorization in China ( Mohamadi et al., 2021 ). Public vaccination discourse at the time focused on side effects of vaccination with close monitoring of adverse events following vaccination ( Gao, Li, He, & Zeng, 2021 ).…”
Section: Methodsmentioning
confidence: 99%
“…Some researchers suggest that parents may still increase investments if their parenting efforts can help their children avoid environmental hazards (Ellis et al, 2009; Quinlan, 2007). In the post‐COVID‐19 era, national vaccination and strict implementation of the national pandemic‐prevention policy in China have significantly reduced the threat of the pandemic to people's lives (El‐Shabasy et al, 2022; Mohamadi et al, 2021). Accordingly, even in the context of an unpredictable future economy, it is still possible for parents to help their children avoid economic difficulties and enhance their development through helicopter parenting.…”
Section: Introductionmentioning
confidence: 99%